Um estudo experimental sobre respostas de solucionar problemas, informar e descrever e suas possíveis relações - Haddad, Ana Luiza Focchi (2008)
The present study aimed to investigate the influence of the separate request of the information and descripton response, when asked isolated in different moments of the experiment, on a problem solving situation. The amount of solicitation to information and description response was held constant (10 opportunities) for most of the groups. The information response consisted in the participant clicking YES or NO at the screen s computer when asked if he/she knows the solution to the exercise. The description response consisted in writing the description of contingencies. 72 subjects humans participated of this study that was divided into nine experimental groups. All participants were exposed to 40 attempts to matching to sample task. Four groups were required only to the information task but this solicitation occurred in different block of attempts. Another four groups were required only to the description task, this request occurred in different blocks of attempts. Only one group was required to information and description tasks, this solicitation occurred after the forty attempts of matching to sample task. The results suggest the higher is the number of attempts of previous exposition before the requests, the better is the performance in the non - verbal task, higher quantities of YES before the right choose at the matching to sample task and higher quantities of correct contingencies description are obtained. On the whole the participants that were request only to the information task had a better performance at the matching to sample task. The regularity of right answers at this task exerted influence on the performance of inform and describe